Novel Crown Cement Containing Antibacterial Monomer and Calcium Phosphate Nanoparticles - Rashed AlSahafi; Abdulrahman A. Balhaddad; Heba Mitwalli; Maria Salem Ibrahim; Mary Anne S. Melo; Thomas W. Oates; Hockin H.K. Xu; Michael D. Weir (Nanomaterials, 2020)
Oral biofilm accumulation at the tooth–restoration interface often leads to recurrent dental caries and restoration failure. The objectives of this study were to: (1) develop a novel bioactive crown cement containing dimethylaminohexadecyl methacrylate (DMAHDM) and nano-sized amorphous calcium phosphate (NACP), and (2) investigate the mechanical properties, anti-biofilm activity, and calcium (Ca2+) and phosphate (PO43−) ion release of the crown cement for the first time. The cement matrix consisted of pyromellitic glycerol dimethacrylate and ethoxylated bisphenol-A dimethacrylate monomers and was denoted PEHB resin matrix. The following cements were tested: (1) RelyX luting cement (commercial control); (2) 55% PEHB + 45% glass fillers (experimental control); (3) 55% PEHB + 20% glass + 25% NACP + 0% DMAHDM; (4) 52% PEHB + 20% glass + 25% NACP + 3% DMAHDM; (5) 51% PEHB + 20% glass + 25% NACP + 4% DMAHDM; (6) 50% PEHB + 20% glass + 25% NACP + 5% DMAHDM. Mechanical properties and ion release were measured. Streptococcusmutans (S. mutans) biofilms were grown on cements, and colony-forming units (CFUs) and other biofilm properties were measured. The novel bioactive cement demonstrated strong antibacterial properties and high levels of Ca2+ and PO43− ion release to remineralize tooth lesions. Adding NACP and DMAHDM into the cement did not adversely affect the mechanical properties and dentin bonding strength. In conclusion, the novel NACP + DMAHDM crown cement has excellent potential for restoration cementation to inhibit caries by suppressing oral biofilm growth and increasing remineralization via Ca2+ and PO43− ions. The NACP + DMAHDM composition may have wide applicability to other biomaterials to promote hard-tissue formation and combat bacterial infection.